Numerical Study Of The Laminer Mixed Convecton In A Ventilated Square Cavity With Baffles (University of Thi-Qar Journal for Engineering Sciences, 2017)
Laminar mixed convective flow in a ventilated square cavity with baffle has been studied numerically using finite element method with software package (FlexPDE). The bottom wall is heated with a constant heat flux and the other walls are adiabatic. The flow is assumed to be two-dimensional. The air enters the cavity through an opening at the bottom of the left wall and exits from another opening at the top of the right wall. Laminar regime is considered under steady state condition. In addition, the two horizontal guide baffle, first baffle was attached from the left vertical wall and the other baffle was attached from the right vertical wall with a constant height Hb1= 0.5L and length Lb= 0.25L and the third baffle was put in the center with different height Hb2= 0.25L, 0.5L and 0.75L and Lb1= 0.4L. A parametric study was performed presenting the influence of; Reynolds' number (50 ≤ Re ≤ 200), Richardson number (0.1≤ Ri≤ 10) and Prandtl number (Pr= 0.71).Results were presented with streamlines, isotherms, Nusselt numbers and average non-dimensional temperature. And the result show the increasing of Nu with increasing Re, Ri and with decreasing the location of the baffle from the bottom wall. A comparison was made between the present work and that obtained by [1]which it reveals good agreement